OPERATIONAL READINESS OF GLOBAL MOBILE SATELLITE COMMUNICATION SYSTEM UNDER PARTIAL AND COMPLETE FAILURE - EKATA; S. B. SINGH (Journal of Engineering Science and Technology, 2011)
The aim of the present paper is to study and examine the various reliability characteristics of a global mobile satellite communication System (GMSCS) with the help of mathematical modelling. GMSCS basically comprises of four subsystems; Space segment, Land earth stations, Telecommunication terminals and Mobile earth stations. The system under consideration can have three different modes of working: normal, partial and complete failure. The system is characterized by determination of probabilities being in ‘up’ and ‘down’ states at any instant. Integro-differential equations are derived for these probabilities by identifying the system at suitable regeneration epochs. Based on the assumption that the failure rates of units are distributed exponentially while the repair rates are distributed arbitrarily, different reliability measures like operational availability, reliability, mean time to failure and cost effectiveness have been computed with the principle of Laplace transforms and supplementary variable technique. Considerable attention is devoted to illustrate the results with numerical examples to highlight the important features of reliability measures of the system.